DINAMIKA PENDIDIKAN MUHAMMADIYAH - Pasmah chandra (Conciencia, 2018)
Muhammadiyah education (Muhammadiyah school) is currently entering the era of competition. Muhammadiyah education must modernize education management. Modernization in the development of Muhammadiyah school management can be done on aspects of curriculum management, management of educators and education, student management and management of facilities and infrastructure. But on the other hand, Muhammadiyah schools are not enough to just develop in the field of school management. Muhammadiyah schools must maintain the existence of Ahmad Dahlan's noble values ​​as spirits from Muhammadiyah schools. Do not let Muhammadiyah schools only have the Muhammadiyah "Brand Board" but precisely the values ​​of Kemuhammadiyahan from the school are nil. The formulation of the problem in this study is how the existence of Ahmad Dahlan's teachings and the modernization of education management at Muhammadiyah schools in South Bengkulu. The purpose of this study was to find out the existence of Ahmad Dahlan's teachings and the modernization of education management at Muhammadiyah schools in South Bengkulu and the dynamics of its development from the beginning to the present. This type of research is qualitative research. The results of the study are; First, Ahmad Dahlan's teachings at the South Bengkulu Muhammadiyah school still exist at both the Elementary and High School levels. The existence of Ahmad Dahlan's teachings can be seen from the subjects of Al Islam and Kemuhammadiyahan taught at school. So is the existence of Ahmad Dahlan's teachings in terms of worship and moral formation of students. Secondly, Muhammadiyah as a renewal education institution always modernizes education management, both curriculum management, student affairs, teaching staff, and facilities and infrastructure. Third, Muhammadiyah South Bengkulu schools always experience dynamics in their development. The Muhammadiyah school was first established in South Bengkulu in 1930. The Muhammadiyah educational institution experienced a phase of development from time to time, there were schools that changed the status of the madrasa ibtidaiyah to primary school. There are also Muhammadiyah schools that are unable to compete so they have to be closed but there are also Muhammadiyah schools that have survived and developed to this day. Fourth, the dynamics of the development of Muhammadiyah schools in South Bengkulu are influenced by internal and external factors.